Evaluating the Accuracy Rates of Clinical and Radiographic Diagnoses Compared with Histopathologic Diagnosis of Oral Exophytic Lesions - Javad Sarabadani; Abbas Javadzadeh; Mahrokh Imanimoghaddam; Nooshin Mohtasham; Maryam Amirchaghmaghi (Mashhad University of Medical Sciences, 2013)
Introduction: The aim of this study was to identify the reasons for failure in clinical, radiographic, and histopathologic diagnoses as well as their interactions with each other. Methods: Personal information and lesion characteristics of 51 patients with central or peripheral exophytic lesions were collected in Mashhad dental school. Specialists determined clinical and radiographic diagnoses and after taking biopsy, the clinical and radiographic diagnoses were compared with histopathologic diagnosis. Results: Fifty three patients with oral exophytic lesions were evaluated among which 66.6% were peripheral and 33.4% were central exophytic lesions. Males constituted 52.9% of the patients while 47.1% were female. The first clinical and radiographic diagnoses were not confirmed with the histopathologic diagnosis in some patients. 80.4% of the first clinical diagnoses were consistent with the pathologic reports and in other cases, the clinical diagnosis were not confirmed histopathologically. In addition, radiographic diagnoses in six patients were not consistent with pathologic diagnosis. Conclusion: Great concordance was observed between clinical and radiographic diagnosis with pathologic reports